Effect of air flow rate and C/N ratio on biological nitrogen removal through the CANON process treating reject water - Mousavi, Seyyed Alireza; Mehralian, Mohammad; Khashij, Maryam; Ibrahim, Shaliza (Taylor & Francis, 2018)
The CANON process is a promising method for nitrogen removal in wastewaters with low organic carbon content like reject water. This study investigated the effect of important factors for optimization of the CANON process through inhibition of nitrite-oxidizing bacteria (NOB). In the acclimation period, complete ammonium removal and 43.3% total N removal were obtained at hydraulic retention time of 12 h, temperature of 30°C ± 0.5°C and DO equal to 7–9 mg/L. The effects of air flow rate (AFR) (representative of DO), SRT and C/N were evaluated. Air flow rate was the most important factor for controlling the process, but the effect of SRT was negligible. When AFR was increased from 100 to 500 mL/min, both ammonium removal efficiency (33–43% to 81–83%) and nitrite accumulation (nitritation, 40 mgN/L to 100–120 mgN/L) were increased, but with increasing AFR to 1000 mL/min only ammonium removal efficiency was increased and because of better condition (high DO) for NOBs, nitritation was decreased. C/N had an effect like AFR of 1000 and only increased ammonium removal efficiency and total N removal. With increasing AFR and C/N, both OUR and AUR were increased, but SVI was decreased.